Muslim Experiential Religiousness: Spirituality Relationships With Psychological and Religious Adjustment in Iran. Issue 4 (1st October 2016) - Ghorbani, Nima; Watson, P. J.; Madani, Maryam; Chen, Zhuo Job
ABSTRACT: Iranian university ( N = 153) and Islamic seminary ( N = 143) students responded to a Muslim Experiential Religiousness measure of spirituality. This instrument correlated positively with Integrative Self-Knowledge, Self-Control, Mindfulness, and Satisfaction With Life. Muslim Experiential Religiousness also displayed direct associations with Muslim Attitudes Toward Religion and with Intrinsic and Extrinsic Personal Religious Orientations. At higher levels of Muslim Experiential Religiousness, Muslim Attitudes Toward Religion displayed stronger connections with psychological and religious adjustment. Islamic seminarians self-reported higher Islamic spirituality than university students. Overall, Muslim Experiential Religiousness appeared to assess a Muslim form of spiritual self-regulation.